An assessment of the groundwater resources based on infiltration recharge hydrogeological modeling - S. O. Grinevskiy; Y. V. Ivanova; A. O. Safonov (Известия высших учебных заведений: Геология и разведка)
An assessment of the natural groundwater resources (GWR) of Devonian (middle and upper Famennian) aquifer was made in the area of research-assessment works for Smolensk city water supply. It was done on the basis of geohydrological modeling of infiltration groundwater recharge, which includes the surface water balance of precipitation and moisture transverse in the aeration zone. This approach allowed estimation of the total value of natural GWR, as well as the quantitative analysis of the heterogeneity of the conditions of their formation and distribution between upper Quaternary and lower Devonian aquifers (in the zone of the intensive water recharge). The values of the estimated GWR are confirmed by the results of geofiltration groundwater flow modeling. The considered approach is the alternative or addition to the well-known method of GWR estimation, based on the river flow analysis.